1983
DOI: 10.2118/10676-pa
|View full text |Cite
|
Sign up to set email alerts
|

The Rules for Achieving High Solubilization of Brine and Oil by Amphiphilic Molecules

Abstract: The oil-recovery effectiveness of a chemical flood has been proved related to the phase behavior of the brine/oil/surfactant system. In particular, it is advantageous to formulate the system so that optimal threephase behavior is obtained. However, it also has been demonstrated that all the optimized systems are not equivalent in terms of solubilization. interfacial tensions (IFT's), and oil-recovery efficiency. This paper addresses the conditions that promote high solubilization in microemulsions, a property … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 28 publications
2
52
0
1
Order By: Relevance
“…Thus the pivot point is inevitably reached by tuning the temperature. Analogous behavior may be observed with variations of salt concentration [52,53], surfactant composition [54], alcohol concentration and oil ACN [55,56] or even pressure and pH in unconventional systems containing a supercritical carbon dioxide oil phase and siloxane-based ionomer surfactant [57].…”
Section: Choice Of the Best Conditions For The Determination Of Eacnsmentioning
confidence: 77%
“…Thus the pivot point is inevitably reached by tuning the temperature. Analogous behavior may be observed with variations of salt concentration [52,53], surfactant composition [54], alcohol concentration and oil ACN [55,56] or even pressure and pH in unconventional systems containing a supercritical carbon dioxide oil phase and siloxane-based ionomer surfactant [57].…”
Section: Choice Of the Best Conditions For The Determination Of Eacnsmentioning
confidence: 77%
“…The full complexity of the effect of the alcohol was unveiled 20 years ago in the S+A vs. formulation diagram schematically reproduced in Figure 12 (71). This figure gathers the gamma diagrams (each represented only as the cross shown around the tricritical point in Figs.…”
Section: Solubilization Enhancement With Multiple Amphihilic Speciesmentioning
confidence: 98%
“…14. In this relation C S * is the “height” (wt%) of the three-phase region close to the OW side in a SOW ternary diagram of the Winsor III triangular type [39, 40], or the minimum concentration to attain the single phase behavior at the tail of the fish, Fig. 7b, sometimes called C X [41], which is another way to express the solubilization so that SP* = (100 −  C S *)/2 C S * (≅ 50/ C S * if the solubilization is high).…”
Section: Relation Between Tension and Solubilization: Performance Indexmentioning
confidence: 99%
“…This analysis was carried out for all possible concomitant dual changes [39, 40, 50] and it was found that the performance is changed only when both numerator and denominator are changed one way or the other, although a few more complex cases arise when a variable alters more than a single term, which is the case with the temperature.…”
Section: Trends To Improve Performancementioning
confidence: 99%